Light Intensity Optimization of a Microcontroller-Based Solar Tracking Panel - Hazrin, Muhammad Hazim; Mohd Hassan, Siti Lailatul; Abdul Halim, Ili Shairah; Sulaiman, Nasri (International Journal of Integrated Engineering, 2025)
This paper is on the light intensity optimization of a microcontroller-based solar tracking panel system, addressing the limited efficiency of fixed solar panels in capturing solar energy. This project aims to improve fixed solar panels by using a tracking system that always follows the sun’s direction using a microcontroller. An automated tracking system for solar panels usually has two types: single-axis and dual-axis. This project studies the light intensity gained from the solar panel based on the tilt angle of the solar panel according to the sun’s movement. The gyroscope is used to gather data on the tilt angle to analyze and compare it to a fixed solar panel at an optimal angle. A DC multimeter measures the voltage and current obtained from the solar panel, and a DC motor moves the panel every 1 hour. At the end of this work, a complete automatic solar tracking system with high efficiency was successfully developed. There is an increase of 9.195% in the efficiency of the power gained by applying the solar tracker system. Therefore, a solar tracker can help improve the efficiency of collecting renewable energy of solar.